(untitled) (International Journal of Ayurveda and Pharma Research, 2015)
Safety is the major concern today. It mainly depends on the method of preparation. To assess the quality of a finished product, there should be some basic standards as well as methods of preparation. Shashilekha Vati is one such Herbo-mineral compound used in the treatment of Vitiligo. A chronic Toxicity Study for Shashilekha Vati carried out in the National Toxicology Centre (N.T.C.) Pune to establish the tolerability and to evaluate the effective and non-toxic human dose of Shashilekha Vati by assessing the histopathological and subjective changes in animals. Young (6-8 wks old) male and female Swiss albino mice (28-32 gms of weight), bred at the N.T.C. were used for the study. The duration of the chronic toxicity study was of 3 months (90 days). Shashilekha Vati was prepared according to the method mentioned in the classical text of Yogaratnakara. During the course of the study, all the animal belonging to the entire different groups were observed for food intake, signs of toxicity, histo-pathological study. Clinical parameters (food intake, body weight, sings of Toxicity) indicate safety of Shashilekha Vati for Human Dose Group. Histological findings for day 90; for Ten Times Human Dose Group showed degenerative changes in the liver and kidneys. While it shows mild to moderate degenerative changes in Ten Times Human Dose. The study showed positive results as the Shashilekha Vati is safe and non toxic when given in human dose.